Development and validation of an Integrated Organizational Safety Climate Questionnaire with multilevel confirmatory factor analysis - Brondino, M.; Pasini, M; Silva, S.A. (Quality and Quantity, 2013)
Meta-analytic and traditional reviews on safety climate reveal theoretical and methodological safety climate issues still open. The main aim of this study is to propose a questionnaire which combines recent and different approaches to safety climate, trying to give a contribute about these issues. The present research led to the development of a new questionnaire to measure safety climate, suitable for blue-collar workers, and to the evaluation of its psychometric properties, and usefulness to measure safety climate in the industrial sector. Multilevel confirmatory factor analysis (MCFA) was used to properly evaluate the factor structure underlying the safety climate questionnaire composed of three scales: organizational safety climate scale, supervisor's safety climate scale and co-workers' safety climate scale. The clear distinction, made with the use of three different scales, among safety agents (organization, supervisor, co-workers), allows the assessment of workers' perceptions focused on each level, and allows to deeply explore, for instance, lateral relationships of supervisor's safety climate and co-workers' safety climate, analysing the interactions between the roles of these two safety agents. A two-level design was used, considering the individual level and the work-group level. Data collection involved 1,617 blue-collars from eight Italian manufacturing companies. The MCFA results demonstrated the importance to use proper analysis to study the factor structure of a multilevel construct as safety climate, and confirmed the theoretical structure of safety climate purposed from Griffin and colleagues, using not only psychological climate (i. e., the individual level), but also the group level safety climate.